WILL SOFT-BONED MILKFISH-A TRADITIONAL FOOD PRODUCT FROM SEMARANG CITY, INDONESIA-BREAKTHROUGH THE GLOBAL MARKET - Tri Winarni Agustini; Indah Susilowati; S Subagyo; Wilis Ari Setyati; Bambang Argo Wibowo (JOURNAL OF COASTAL DEVELOPMENT, 2010)
One of the famous traditional food products from Semarang city is softboned-milkfish (called as bandengpresto). In national level, Bandeng Presto is the trade mark of Semarang City. Bandeng presto are producedby several outlet in Semarang from small to large in scales. The products are vary, in term of variety,quality, processing technique, packaging and prices. The small-scaler produces less in quality standard,safety, packaging, and marketing system. Nevertheless, there are several small-scaller outlets are able toreach the international market after they promoted their product through webside or internet. The objectivesof the study were to develop the improved quality in production techniques, lay out designed, and themarketing strategy for bandeng presto in Semarang city to support the regional food security and food safety.The results indicated that nutritional content of bandeng presto are good in general and can be considered asgood nutritional resource for human. Raw material and processing technique influence the nutrition value ofthe product. Based on market survey suggests that bandeng presto is more efficiently promoted throughwebsite, especially to touch the long distance customers. In addition, improved in packaging design and inlabelling (recently for exposing information on EPA and DHA of the product) will help customers to assurethe quality of the product properly.